Elevated coagulation factor VIII and the risk for recurrent early pregnancy loss - Dossenbach-Glaninger, Astrid; van Trotsenburg, Michael; Krugluger, Walter; Dossenbach, Martin R.; Oberkanins, Christian; Huber, Johannes; Hopmeier, Pierre (Thrombosis and Haemostasis, 2004)
Inherited and acquired thrombophilia are associated with recurrent pregnancy loss. Recently, an increased risk for thromboembolic disease was described for patients with elevated coagulation factor VIII, but it is unknown whether there is also an association to early pregnancy loss. We therefore evaluated the relation between recurrent early pregnancy loss and levels of coagulation factor VIII. We enrolled 49 unrelated Caucasian women with a history of 2 6 early pregnancy losses and 48 healthy controls, who had delivered at least one term infant and had never experienced pregnancy loss. We determined factor V Leiden-, G20210A prothrombin-, MTHFR C677Tand A1298Cgene mutations, levels of antithrombin, protein C, protein S, factor VIII, C-reactive protein and antiphospholipid antibodies. There was a significantly higher rate of pregnancy losses in women with Antiphospholipid Syndrome (p = 0.043). Furthermore, plasma levels of coagulation factor VIII were significantly higher in cases than in controls (130.5 IU/dl ± 25.4 vs 119.5 IU/dl ± 24.1; p = 0.032) and appeared independent of Creactive protein (R = 0.146, p = 0.323 in cases; R = 0.028, p = 0.850 in controls). The relative risk for recurrent pregnancy loss in women with factor VIII levels above 151 IU/dl (90th percentile of controls) was 2.5 (0.7 – 8.9, 95 percent confidence interval), for levels above 156 IU/dl (95th percentile of controls) 3.9 (0.8 – 20.0, 95 percent confidence interval). Elevated maternal plasma levels of coagulation factor VIII tend to be associated with an increased risk for recurrent early pregnancy loss.
Keywords: Antiphospholipid syndrome; coagulation factor VIII; pregnancy loss; thrombophilia